Deaths Due to Electrocution- A Retrospective Study (Medico Legal Update, 2019)
Retrospective analysis of deaths because of electric shock from the medico-legal death records our collegei.e. J.N.M.C., A.M.U., Aligarh, Uttar Pradesh, India. Most of the deaths were of men having the age inbetween 11-50 years. All deaths were inadvertent and most part of them were during the time of monsoon ascompared to the deaths in western countries where, baths, warmers or hair dryers were the source of electricshocks. The death rate reported because of electric shock was 0.34 per lakhs (100000) of the populationin the present study as against the figures of 0.94 and 0.14 from Bulgaria and Canada respectively. A largeportion of the deaths were either prompt or quick. It implies that individuals living at home did not havebasic knowledge of dangers of electric shock. In this way mindfulness about utilization of good qualityelectric machines is the need of great importance.